Multifunctional dual-layer microneedles loaded with selenium-doped carbon quantum dots and Astilbin for ameliorating diabetic wound healing - Zhen Zhang; Yulin Zhang; Liang Peng; Yi Xing; Xinru Zhou; Shuo Zheng; Yanli Zhang; Longquan Shao (Materials Today Bio)
Diabetic wounds (DW) represent a significant clinical challenge due to chronic inflammation, excessive oxidative stress, and impaired angiogenesis, all of which hinder effective tissue regeneration. Existing drug delivery systems often fail to achieve sustained and targeted therapeutic efficacy. In this study, we developed a novel dissolvable dual-layer methacrylated gelatin (GelMA) microneedle (MN) co-loading selenium-doped carbon quantum dots (Se-CQDs) and Astilbin (AST) for enhanced DW treatment. The outer layer, enriched with Se-CQDs, rapidly scavenges reactive oxygen species (ROS), effectively alleviating oxidative stress at the wound site. Sequentially, the inner layer releases AST, exerting potent anti-inflammatory and pro-angiogenic effects. Preliminary findings suggest these effects may involve the modulation of cytoskeletal dynamics and peroxisome function, contributing to endothelial cell migration and angiogenesis. This controlled, sequential release MN establishes a low-oxidative, anti-inflammatory microenvironment, thereby promoting angiogenesis and accelerating wound repair. The pioneering integration of selenium-doped quantum dots and AST-loaded hydrogels offers a synergistic therapeutic strategy, setting a new standard for advanced diabetic wound care with substantial clinical promise.